2017
DOI: 10.1257/app.20160267
|View full text |Cite
|
Sign up to set email alerts
|

In a Small Moment: Class Size and Moral Hazard in the Italian Mezzogiorno

Abstract: Instrumental variables (IV )estimatesS chool improvement efforts often focus on inputs to education production, the most important of which is staffing ratios. Parents, teachers, and policymakers look to small classes to boost learning. The question of whether changes in class size have a causal effect on achievement remains controversial, however. Regression estimates often show little gain to class-size reductions, with students in larger classes sometimes appearing to do better (Hanushek 1995). At the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 41 publications
2
65
1
Order By: Relevance
“…This additional restriction helps to account for the potential score manipulation in primary schools. Angrist, Battistin and Vuri () used data from INVALSI tests for the years 2009–12 and demonstrated that – especially in southern Italy – small classes increase the manipulation of test scores. They suggested that, if small classes are increased by ten students, this can reduce the manipulation of test scores by the order of 5 per cent .…”
Section: Empirical Methodologymentioning
confidence: 99%
“…This additional restriction helps to account for the potential score manipulation in primary schools. Angrist, Battistin and Vuri () used data from INVALSI tests for the years 2009–12 and demonstrated that – especially in southern Italy – small classes increase the manipulation of test scores. They suggested that, if small classes are increased by ten students, this can reduce the manipulation of test scores by the order of 5 per cent .…”
Section: Empirical Methodologymentioning
confidence: 99%
“…INVALSI test scores are intended to evaluate pupils' as well as teachers' performance. Hence, it could be reasonable to suspect that some teachers could help their students when doing tests in order to achieve a better evaluation for the entire classroom (see Bertoni, Brunello, andRocco 2013 andAngrist, Battistin, andVuri 2014 for relevant studies on the topic using INVALSI data). In our specific case, however, the issue is likely to play a very minor role since our main strategy relies on comparison between groups of pupils that differ from each other only by 1 month of age, so that there is no reason to think that one group is affected by cheating phenomena differently from the other one.…”
Section: B Normative Framementioning
confidence: 99%
“…Our estimation approach resembles the analysis of Boston's Metco desegregation program by Angrist and Lang (2004) in that it uses distinct sources of variation to identify the separate effects of interest (differences in types of policy and study goals to one side). Across a variety of settings, studies in the class size literature have found positive effects on achievement (for instance, Krueger 1999, Angrist and Lavy 1999, Krueger and Whitmore 2001, and Gilraine 2020 as well as no effects (including Hoxby 2000 andAngrist, Battistin andVuri 2017). Research studying the Californian context has delivered mixed results similar to the broader literature (see Unlu 2005 andJepsen andRivkin 2009 for positive test score effects and Bohrnstedt and Stecher 2002 for non-effects).…”
Section: Introductionmentioning
confidence: 97%